Effect of Age at Menarche on Anterior Cruciate Ligament Injury Incidence and Anterior Knee Laxity in Collegiate Athletes - Froehle, Andrew; Cox, Joseph; May, Jedediah; Grannis, Kimberly; Duren, Dana (Bowling Green State University, 2020)
Female athletes suffer painful, costly, and career-limiting non-contact anterior cruciate ligament (ACL) injuries more often than males. Previous research suggests that pubertal neuromusculoskeletal development contributes to this sex-bias, but the manner in which variation in pubertal development affects injury risk within females is poorly understood. Age at menarche is a variable, significant pubertal developmental event, signaling the onset of estrogen cycling and affecting musculoskeletal development. Earlier menarche may increase injury risk, possibly by increasing anterior knee laxity through prolonged estrogen exposure. The purpose of this case-control study was to test the primary hypothesis that collegiate athletes with previous ACL injuries have earlier age at menarche than their uninjured peers, and to test the secondary hypothesis that earlier menarche is related to greater anterior knee laxity in injured and uninjured athletes. The study sample consisted of female NCAA Division-I varsity athletes (N=14 injured, N=120 uninjured). Outcome measures included: menstrual history and ACL injury details (injury age, activity at time of injury, contact vs. non-contact), assessed by questionnaire; and anterior knee laxity assessed by KT-1000 arthrometer. Correlation, t-tests, and regression analysis were used to test for associations between age at menarche, injury incidence, and knee laxity. Fourteen athletes reported ≥1 non-contact ACL injury, and had significantly earlier menarche than uninjured athletes (12.6±1.3 y vs. 13.4±1.4 y; P=0.05). Earlier menarche also significantly predicted injury status (Wald c2=7.43; Pb=-1.02±0.37; OR=0.36; 95% CI:0.17-0.75), but was not correlated with anterior knee laxity. Within injured athletes, however, laxity in the unaffected knee was significantly related to time since menarche (r2=0.79, Pr2=0.72, P